Role of mediation in resolving community disputes - Abdul Hak, Nora (2019)
The social background of Malaysia as a multicultural and multi ethnic country. The interaction and integration is somewhat dependent upon the knowledge and understanding of the various cultures, languages and religions. Every single issue involving different racial and religious groups is sensitive and should be handled diligently. Malaysia should have its own mechanism towards national integration and dispute resolution is definitely a major priority. CM is considered as the best method since the mediator will have to rely on the ethnic and racial identities to interpret the interpersonal problems and thus, achieve a fair result to all the parties. Malaysia should revive its tradition that had been replaced by litigation by introducing CM and expose the people of self empower which should be a better way to deal with their dissatisfaction and needs rather than leaving them in the hand of authority to deal with their disputes.